Haemorrheological effects of prostaglandin E1 infusion in Raynaud's syndrome. Issue 8 (August 1984) - Lucas, G S; Simms, M H; Caldwell, N M; Alexander, S J; Stuart, J
Abstract : Eighteen patients with severe Raynaud's syndrome had impaired deformability of erythrocytes, as measured by filtration through 5 micron diameter pores, compared with 19 healthy controls. The patients were given prostaglandin E1 (PGE1) or placebo by intravenous infusion for 72 h to assess the haemorrheological action of PGE1. Contrary to a previous report, PGE1 did not improve erythrocyte filterability. Infusion of PGE1 did, however, evoke an acute phase response with hyperproteinaemia and a leucocytosis and is a potentially important mediator of this stress response in patients with vascular disease.